Feminisms and Ruralities. - Pini, Barbara (Lexington Books, 2014)
This book aims to question, recalibrate and expand the field of rural social science by attending to the current debates in rural studies and feminist studies and by identifying possibilities for taking a rural view of feminisms and a feminist view of ruralities.